Effect of Soil Geochemical on The Chemical Properties of Lignocellulosic Oil Palm Fibers - Tetti Novalina Manik; Sri Wahyuni; Nurul Hikmah; Ahmad Bakri; Simon Sadok Siregar (Lambung Mangkurat University Press, 2023)
Correlation of geochemical of soil and chemical properties of oil palm fiber from the trunk, empty fruit bunches and fronds has been investigated. Frond samples come from dryland and wetland to have more significant results. The chemical properties of topsoil and lignocellulosic fiber were investigated by FT-IR. The geology of soil was investigated by 1D Geoelectric. Measuring of the content of cellulose and lignin according to SNI 14-0444-1989 and SNI 0492-1989-A. Base on research, the geochemical properties of soil are correlated with the chemical properties of the lignocellulosic fiber of the oil palm trees. The cellulose content of wetlands fiber has the lowest than other fibers. This is caused by soil nutrients which are composed of carbonyl and phenolic compounds. Alkalization treatment on the fiber has increased the cellulose content of each fiber. The alkalization treatment increases the adhesive properties. Based on the geology and chemical properties of soil, the land of oil palm trees is composed of clay minerals composed of Si-O-Si, carbonyl, phenol bonds and others.